2014
DOI: 10.3390/ijerph111010883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viewing vs. Not Viewing a Real Forest on Physiological and Psychological Responses in the Same Setting

Abstract: We investigated the impact of viewing versus not viewing a real forest on human subjects’ physiological and psychological responses in the same setting. Fifteen healthy volunteers (11 males, four females, mean age 36 years) participated. Each participant was asked to view a forest while seated in a comfortable chair for 15 min (Forest condition) vs. sitting the same length of time with a curtain obscuring the forest view (Enclosed condition). Both conditions significantly decreased blood pressure (BP) variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 52 publications
(98 reference statements)
3
68
0
2
Order By: Relevance
“…Hb concentrations received by detector 1 were subtracted from those received by detector 2. This procedure allowed us to minimize the influence of skin blood flow (Ando et al, 2013; Horiuchi et al, 2014a), and to provide a NIRS signal traversing approximately 20 mm, because it has been reported that NIRS signals can reach a half of the depth of the distance between the probe and detector (Patterson et al, 1989). …”
Section: Methodsmentioning
confidence: 99%
“…Hb concentrations received by detector 1 were subtracted from those received by detector 2. This procedure allowed us to minimize the influence of skin blood flow (Ando et al, 2013; Horiuchi et al, 2014a), and to provide a NIRS signal traversing approximately 20 mm, because it has been reported that NIRS signals can reach a half of the depth of the distance between the probe and detector (Patterson et al, 1989). …”
Section: Methodsmentioning
confidence: 99%
“…About one third of the studies [23,[26][27][28][29]32,34,39] offered forest therapy programs and control conditions (such as activities in downtown) every other day during the two-day periods. Three studies [12,21,25] used a one-time intervention that lasted a few hours to half a day. One study did not report duration details of the intervention [36].…”
Section: Format and Content Of Forest Therapymentioning
confidence: 99%
“…For articles published in English, nine studies [12,19,21,22,25,28,29,34,39] used POMS to assess the level of depression and three studies [28,29,39] used Semantic differential (SD) method. Other scales used by the studies included the Hamilton Rating Scales for Depression [20], Beck Depression Inventory (BDI) [16,20,24,31], positive and negative affect schedule (PANAS) [34].…”
Section: Depression Measuresmentioning
confidence: 99%
See 2 more Smart Citations